2018
DOI: 10.1158/1078-0432.ccr-17-3717
|View full text |Cite
|
Sign up to set email alerts
|

TERT Promoter Mutation Detection in Cell-Free Tumor-Derived DNA in Patients with IDH Wild-Type Glioblastomas: A Pilot Prospective Study

Abstract: We conducted a pilot study to assess the feasibility and the potential implications of detecting promoter (p)-mutant cell-free tumor-derived DNA (tDNA) in the cerebrospinal fluid (CSF) and plasma of glioblastoma patients. Matched CSF and plasma samples were collected in 60 patients with glial tumors. The CSF collection was obtained during surgery, before any surgical manipulation of the tumor. The extracted tDNA and corresponding tumor DNA samples were analyzed for p and isocitrate dehydrogenase ( hotspot muta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 32 publications
1
53
0
Order By: Relevance
“…However, a number of problems (such as unstable TERT mRNA and enzymatic activity) impede reliable utility of a direct TERT expression or telomerase activity assay for cancer diagnostic or monitoring purpose, whereas widespread TERT promoter mutations in different tumors pave new avenues [31]. The non-invasive detection of a mutant TERT promoter is especially attractive and has been evaluated in plasma, urine and cerebrospinal fluid (CSF) for the diagnosis/monitoring of HCC, bladder cancer and glioblastoma, respectively [31,[87][88][89][90]. These proof-of-concept studies have shown usefulness of the mutant TERT promoter as a non-invasive assay biomarker for these malignancies.…”
Section: Clinical Implications/applications In Precision Oncologymentioning
confidence: 99%
“…However, a number of problems (such as unstable TERT mRNA and enzymatic activity) impede reliable utility of a direct TERT expression or telomerase activity assay for cancer diagnostic or monitoring purpose, whereas widespread TERT promoter mutations in different tumors pave new avenues [31]. The non-invasive detection of a mutant TERT promoter is especially attractive and has been evaluated in plasma, urine and cerebrospinal fluid (CSF) for the diagnosis/monitoring of HCC, bladder cancer and glioblastoma, respectively [31,[87][88][89][90]. These proof-of-concept studies have shown usefulness of the mutant TERT promoter as a non-invasive assay biomarker for these malignancies.…”
Section: Clinical Implications/applications In Precision Oncologymentioning
confidence: 99%
“…The analysis of the CSF ctDNA of a cohort of diffuse gliomas indicated that they could be subtyped by analysing the IDH1 and IDH2, ATRX, TP53, TERT, H3F3A and HIST1H3B mutational status, facilitating the classification of diffuse gliomas and providing prognostic information [28]. Moreover, the presence of mutations in the TERT promoter found in CSF ctDNA correlated with outcome [37]. In the case of diffuse midline gliomas, the detection of H3F3A and HIST1H3B mutations in the CSF could confirm diagnosis [28].…”
Section: Diagnostic Considerationsmentioning
confidence: 99%
“…Physiologic factors include those that limit the amount of tumorderived cfDNA present in the CSF. Multiple studies have shown that low grade tumors or those not directly communicating with the CSF space have low to undetectable tumor-derived cfDNA in the CSF Juratli et al, 2018;Martínez-Ricarte et al, 2018;Pan et al, 2019). Likewise, detection of tumor-derived cfDNA is less likely in patients with new onset disease (Pan et al, 2019).…”
Section: Preanalytical Variablesmentioning
confidence: 99%